Influence of Adult Attachment on Mental Well-being in Young Adults - Mayangsari, Anggi; Reswara, Ilham Phalosa; Kusumawardhani, Sri Juwita; Ariantika, Vivi (Journal of Research and Measurement in Psychology: JPPP, 2024)
Mental health problems in young adults continue to increase in Indonesia, especially problems related to relationships with others. This study aims to examine the effect of adult attachment on mental well-being in young adults. Data collection was conducted in the form of a survey using the Adult Attachment Style Questionnaire and The Warwick-Edinburgh Mental Well-Being Scale. Participants in this study were 302 people aged 18 to 40 years who lived in Jabodetabek. The data analysis used multiple linear regression. The results of this study indicate that overall attachment style has a significant effect on mental well-being. Secure attachment (χ²(1) = 272.02, p <.001) and dismissing attachment (χ²(1) = 15.08, p <.001) both significantly contributed to predicting mental well-being, while fearful attachment (χ²(1) = 11.37, p = .001) and preoccupied attachment (χ²(1) = 4.58, p = .032) had a significant negative influence on mental well-being. These findings will provide implications for improving the mental well-being of young adults by considering their attachments in adulthood and can be a reference for professionals to develop psychological interventions for mental well-being.